Implantación De Una Contabilidad De Costos Por Órdenes De Producción En La Empresa De Adoquines Y Bloques “Durablock” De La Ciudad De Loja, Durante El Período Enero-Marzo Del 2013” - Carrión Pogo, Jessica Verónica (2016)
his thesis entitled " IMPLEMENTATION OF COST ACCOUNTING FOR ORDERS PRODUCTION COMPANY PAVING BLOCKS DURABLOCK Loja CITY DURING THE PERIOD JANUARY- MARCH 2013 " , whose objectives were directed to : Make an inventory based on the information provided, which will display the stocks held by the company for the development of its core business, develop accounting records to facilitate the recognition of the elements of cost, manufacturing process , and preparing financial statements by information provided by the accounting process . The methodology used in developing the implementation of cost accounting was taken into consideration the book of Antonio Molina Calvache which shows how to take proper control of costs and distribution , for which the raw material was used the Kardex cards which allowed to keep track of the inputs and outputs of materials used in the manufacture of the product, in the same way the orders of requisition of materials in which materials were needed detailing was used for each order of production, Manpower time cards for each worker and thus preparing the worksheet in which the time spent in direct labor , indirect labor and downtime in each production order was used is summarized and finally the manufacturing overhead costs which costs budget was developed and distributed it according to the units produced in each production order . Among the results obtained , it became clear that the company DURABLOCK Pavers and Blocks were developed in the period under 53,100 units between blocks and pavers , investing $ 19,347.42 in raw material , labor $ 8,582.99 , indirect costs manufacturing applied $ 1,496.05 and $ 2,116.78 actual costs and there is a change in the cost of $ 620.73 , this is 5 because the company does not have permanent staff in the same way there unnecessary acquisition of raw material what remains in the hold , in terms of sales totaling $ 28,881.00 was obtained and product costs of $ 20,243.02 and generating a profit of $ 2.750.37 exercise , so it is not very profitable due to the high costs that the enterprise holds not take the appropriate management resources decisions. Finally after making all the control registers at different stages of the production is managed properly determine the unit cost of each product which on average was 0.37 cents. the same dollar that is unprofitable for the owner because their sale reaches up to 0.42 cents. Thus the owner to take into account the control registers of each of the cost elements to be provided to determine the cost of production is recommended.